Time Varying Channel Estimation for Amplify-and-Forward Relay Network - Rabbi, M. F.; Yusnita, Rahayu; Kamarul Hawari, Ghazali (2015)
For high Doppler spread channel scenario, in this paper, we develop a channel estimation method for Orthogonal Frequency Division Multiple Access (OFDMA) based Amplifyand-Forward (AF) relay network. Specifically, using Basis Expansion Model (BEM) the fast time varying channels in Source-Relay and Relay-Destination links are approximated. Then a Least Square (LS) and a Linear MMSE (LMMSE) based algorithm is applied to estimate BEM coefficients which are used for channel reconstruction later. Then, we simulate some practical cases of user mobility. Simulation results indicate that the proposed estimators perform consistently in high Doppler spread scenario.